Determinants of Profitability in Smallholder Beef Cattle Farming: Evidence from Langkat Regency, Indonesia - Ruth Dameria Haloho; Suci Andanawari; Kiagus Muhammad Zain; Fauzul Azhimah; Widya Satya Nugraha; Tulus Fernando; Suriansyah - (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
Beef cattle farming is one of the livestock sectors that plays an important role in food security and economic growth. This study aims to identify the production factors that affect the profitability of beef cattle farmers in Langkat Regency. The research method used was a survey, with multistage random sampling as the sampling technique. The respondents were 80 beef cattle farmers. Data collection methods included observation and direct interviews with the farmers. The statistical test used was multiple linear regression using SPSS. The results demonstrate that feed cost, artificial insemination (AI) cost, labour cost, and farmer age have a significant impact on farm profit. The results demonstrate that feed cost, artificial insemination (AI) cost, labour cost, and farmer age have a significant impact on farm profit. In part, feed cost, AI cost, labor cost, and farmer age all significantly affect profitability. Feed costs account for 54.46% of total production costs, followed by labor (41.11%) and AI (4.43%). The results indicate that the key cost items are determinants for beef cattle profitability. Furthermore, to the extent that older farmers tend to be less profitable, farmers’ age has a negative and significant effect on profitability. This association could be explained by higher resilience to change, lesser management adaptability, and limited digital proficiency, which themselves impair access to information and business opportunities through digital means.